1998
DOI: 10.1046/j.1365-294x.1998.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐based genetic differentiation in the aphid Aphis gossypii Glover, evidenced from RAPD fingerprints

Abstract: Samples of the aphid Aphis gossypii (Glover) were collected from different host plants at 18 locations in southern France, La Réunion, Portugal and Laos. RAPD (random amplified polymorphic DNA) patterns of the 480 aphids were obtained using three random primers. A large number of RAPD bands were shared by all aphids of the 18 populations, but some RAPD bands appeared to be population specific. Over all aphids, a total of 37 polymorphic bands were identified and defined 142 RAPD phenotypes. A cluster analysis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 25 publications
4
72
0
1
Order By: Relevance
“…Both indicate that clonal amplification is a major phenomenon shaping the genetic structure of aphids caught in aerial traps. This characteristic of aphid populations has also been observed in all aphid species analysed so far (eg De Barro et al, 1995;Sunnucks et al, 1997;Fenton et al, 1998;Vanlerberghe-Masutti and Chavigny, 1998;Simon et al, 1999;Wilson et al, 1999;Haack et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Both indicate that clonal amplification is a major phenomenon shaping the genetic structure of aphids caught in aerial traps. This characteristic of aphid populations has also been observed in all aphid species analysed so far (eg De Barro et al, 1995;Sunnucks et al, 1997;Fenton et al, 1998;Vanlerberghe-Masutti and Chavigny, 1998;Simon et al, 1999;Wilson et al, 1999;Haack et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Several studies have revealed greater amounts of genetic variability among aphid populations (eg RAPD-PCR, DNA-microsatellite; Vanlerbergh-Masutti and Chavigny, 1998;Wilson et al, 2002;Llewellyn et al, 2003), and hence offer the potential to further assess host-associated genetic differentiation (Lushai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Populations of S. avenae, confined to specific host plants, have been identified using RAPD (De Barro et al, 1995;Lushai et al, 2002) and microsatellite (Sunnucks et al, 1997a) markers, as well as generalists occupying several different hosts (Sunnucks et al, 1997a;Lushai et al, 2002). RAPD markers, have also revealed distinct populations of Aphis gossypii (Glover) on curcurbit and non-curcurbit hosts (Vanlerberghe-Masutti and Chavigny, 1998) and, in conjunction with mitochondrial DNA, Therioaphis trifolii (Monell) on clover and lucerne (Sunnucks et al, 1997b).…”
Section: Nj Miller Et Almentioning
confidence: 99%